From Performance Measurement to Strategic Management Model: Balanced Scorecard - Savsar, Cihat (Journal of Economic Development, Environment and People, 2015)
Abstract: In Today’s competitive markets, one of the main conditions of the surviving of enterprises is the necessity to have effective performance management systems. Decisions must be taken by the management according to the performance of assets. In the transition from industrial society to information society, the presence of business structures have changed and the values of non-financial assets have increased in this period. So some systems have emerged based on intangible assets and to measure them instead of tangible assets and their measurements. With economic and technological development multi-dimensional evaluation in the business couldn’t be sufficient. Performance evaluation methods can be applied in business with an integrated approach by its accordance with business strategy, linking to reward system and cause effects link established between performance measures. Balanced scorecard is one of the commonly used in measurement methods. While it was used for the first time in 1992 as a performance measurement tool today it has been used as a strategic management model besides its conventional uses. BSC contains customer perspective, internal perspective and learning and growth perspective besides financial perspective. Learning and growth perspective is determinant of other perspectives. In order to achieve the objectives set out in the financial perspective in other dimensions that need to be accomplished, is emphasized. Establishing a causal link between performance measures and targets how to achieve specified goals with strategy maps are described.